Optimization of the Role of the Parent Waste Bank as a Solution to Handling Household Waste in Palangka Raya - Puspita, Puspita; Saman, Muhammad; Istiqomah, Anggi Nurhidayah (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2023)
One of the big problems experienced by cities in Indonesia is waste management. The Reduce, Reuse, Recycle (3R) waste reduction activity still has major obstacles, due to low awareness in waste management. One solution that can be implemented is through efforts to develop a Garbage Bank. The existence of a waste bank in Palangka Raya City has been implemented, but the use and utilization by the community has not been maximized. This community service aims to reveal the role of the main waste bank in handling household waste in Palangka Raya City. This type of community service is descriptive-analytic, with primary and secondary data. The results of the community service show that the existence of a main waste bank is very helpful for the surrounding community in waste management, in addition to waste management, the waste bank also provides the surrounding community as customers of the bank. In optimizing the main waste bank for Palangka Raya City, public awareness and the role of the government are needed in providing adequate equipment in the waste management process at the waste bank.